PENERAPA MODEL PEMBELAJARAN KOOPERATIF TIPE INSIDE-OUTSIDE-CIRCLE UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 034 TARAIBANGUN - Aprianti, Riska; Antosa, Zariul; Lazim, Lazim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is based on the low learning outcomes of science subject "ilmu pengetahuan alam (IPS)” of students grade 4th of SDN 034 Taraibangun, with grade average 65,825, while the minimum exhaustiveness criteria "kriteria ketuntasan minimal (KKM)” for IPS is 70. Among 40 students, only 14 students who reached KKM with 35% classical completeness. This research used classroom action research "classroom action research" (PTK) on two cycles which aimed to improve IPS learning outcomes of students grade 4th of SDN 034 Taraibangun,by implementing Inside-Outside-Circle (IOC). The research subjects is students grade 4th SDN 034 Taraibangun. The research data were taken from observation and test. Data analysis technique used is descriptive statistical technique. The result of this research showed that the achievement of teacher activity in the first cycle 79,16%, and the second cycle is 95,83%. Students activities increased too. Students activities in first cycle is 62,5%, and the second cycle is 66,66%. Meanwhile, the average of IPS learning in the first cycle is 75,83 and in the second cycle is 82,41. Classical completeness in the first cycle is 90% increase to 92,5% in the second cycle. From this result it can be concluded that by apply IOC learning model in science studies can increase learning result of students in 4th grader class of SD N 034 Taraibangun.Keywords : Inside-Outside-Circle (IOC) type cooperative model